Chemistry and Biological Activity of Anthraquinones from Morinda Elliptica (Rubiaceae) - Ismail, Nor Hadiani (1999)
Morinda ellipfica or locally known as "mengkudu kecil" is a medicinal plant commonly used by the Malays i n Peninsular Malaysia. The plant parts are used in various ways to treat many health problems and ailments. Literature search did not reveal any reports on its chemical constituents or biological activity. So, it is believed tl1at this is the first study on the chemical constituents and biological activity of Morinda ellipfica. Phytochemical studies on roots of this plant have resulted in the isolation of a new anthraquinone, 2-formyl-1-hydroxyanthraquinone, and ten known anthraquinones, 1-hydroxy-2-methylanthraquinone, nordamnacanthal, damnacanthal, lucidin-w-methylether, rubiadin, soranjidiol, morindone, rubiadin-1-methylether, morindone-5-methyl ether and a lizarin-1-methylether. The structures of the anthraquinones were established based on spectral studies using ultravioletvisible spectroscopy, infrared spectroscopy, one and two dimensional nuclear magnetic resonance spectra, and mass spectrometry.The new anthraquinone, 2-formyl- -hydroxyanthraquinone, was synthesized through a four step synthesis from phthalide anhydride and 4-bromophenol. The steps involved a Friedel-Crafts condensation of the starting mate rial to form the anth raqu inone rings followed by debromination and methylation before an oxidation step to the targeted aldehyde. Studies on the biological activity of the anthraquinones were conducted using some selected bioassay procedures. The anthraquinones were subjected to a battery of bioactivity testings, which included antimicrobial, antiviral, cytotoxicity and antioxidant assays. The results of these tests indicated that some of the compounds do possess interesting biological activity especially in the cytotoxicity and antioxidant assays. Damnacanthal and nordamnacanthal were found to be active against many cell lines tested and may have potential to be developed as anticancer agents.